Effects of the liaison nurse management on the infectious stroke complications: a randomized controlled trial - Zohreh Kalani; Sedigheh Ebrahimi; Hossein Fallahzadeh (BMC, 2022)
Abstract Background Two of the most serious complications after stroke are pneumonia, and urinary tract infection. Liaison nurse, from hospital admission to discharge and then at home helps patients with complicated caring issues stroke. This study investigates the effect of liaison nurse management on the incidence of pneumonia and urinary tract infection in patients with stroke after discharge from the hospital. Methods This randomized controlled trial was conducted on 80 patients in a hospital in Iran. The intervention group was assessed and developed a caring program by the liaison nurse and the control group received routine care. Two weeks and two months after discharge, the patients were evaluated for the incidence of pneumonia and urinary tract infection. Collected data were analyzed using the Chi-square test. P < 0.05 was considered statistically significant. Results The two groups were homogenous in terms of mean age; gender frequently distribution and having urinary catheter. The incidence of pneumonia in intervention and control groups (11.6% vs. 19.2%, P = 0.35) had no statistically significant differences, but there was a significant difference in the incidence of urinary tract infection (0% vs. 24.6%, P < 0.001). Conclusions With liaison nurse performance, there was a significant difference in the incidence of urinary tract infection, in two months after discharge from hospital, but the incidence of pneumonia had no statistically significant differences in two groups. Nurse's evaluation each patient individually according to needs, developing and monitoring the home-based care program, beyond overall education to these patients, could reduce some of complications of a stroke. Trial registration This study is retrospectively registered by Iranian Registry of Clinical Trials with decree code: IRCT20170605034330N3 on April 4, 2018.